Kinetic regularities of the formation of gas products under the influence of ionizing radiation on biomass - Khalilov, Z.Z.; Mahmudov, H.M. (Вопросы атомной науки и техники, 2019)
The kinetic dependence of molecular hydrogen and other gases emergence out of biomass (oak, beech, pine) by a radiation-thermal method has been studied at the temperature T = 673 K. It has been determined that at the rate of D < 10 kGy of the absorbed dose the amount of hydrogen and light hydrocarbon gases in the composition of the gas products emerged out of biomass is slightly higher. At the subsequent rates of continuous radiation (D ≥ 10 kGy) the increase in the amount of hydrocarbons with heavy molecular mass contained in gas occurs as a result of dimerization or trimerization of the emerged radicals. It was presented short mechanism of biomass conversion under ioni-zing radiation. Досліджено кінетичну залежність отримання молекулярного водню та інших газів з біомаси (дуба, бука і сосни) при температурі Т = 673 К радіаційно-термічним шляхом. Незважаючи на те, що кількість газоподібного водню і легких вуглеводнів була високою в біомасі при поглиненій дозі D < 10 кГр і безперервному опроміненні, у високих оцінках поглиненої дози D ≥ 10 кГр кількість важких молекулярних вуглеводнів збільшується за рахунок димеризації або тримеризації радикалів. Исследована кинетическая зависимость получения молекулярного водорода и других газов из биомассы (дуба, бука и сосны) при температуре Т = 673 К радиационно-термическим путем. Несмотря на то, что количество газообразного водорода и легких углеводородов в биомассе было высоким при поглощенной дозе D < 10 кГр и непрерывном облучении, в высоких оценках поглощeнной дозы D ≥ 10 кГр количество тяжелых молекулярных углеводородов увеличивается в результате димеризации или тримеризации радикалов.